Graphical User Interface for the Control of a Biped Robot - Urrea-Onate, E (IGI Global, 2019)
The design and implementation of a graphical user interface (GUI) for the control and operation of a biped robot is presented. This GUI allows establishing communication between the user, the robot and a computer (controller) so that the robot can perform bipedal walking without the need to introduce commands that are not user-friendly. The developed graphic interface permits the user to carry out tasks operating on the robot without having to resort to commands that are not easy to use. This interface was created using the MATLAB-Simulink software and it presents important advantages compared to the manual operation of a robot. © 2019, IGI Global.